Budaya Seiri, Seiton, Seiso, Seiketsu, dan Shitsuke di Industri Kecil Menengah Kerupuk Azizah - Dina Rahmayanti; Feri Afrinaldi; Reinny Patrisina; Yumi Meuthia; Hilma Raimona Zadry; Lusi Susanti; Prima Fithri; Desto Jumeno; Luthfi Fakhri Ramadhan (Warta Pengabdian Andalas, 2023)
This community service activity was carried out by designing a cabinet for finished products and handing over the cabinet to a small and medium industry producing various types of crackers, namely IKM Kerupuk Azizah. IKM Kerupuk Azizah used open shelves to store packaged finished products. This practice was unhygienic and risky. Animals like rats and insects ate and damaged the materials and products. In addition, the warehouse needed to look more tidy. Moreover, from an aesthetic point of view, it was unattractive. A storage cabinet was designed to solve this problem. In designing the cabinet, available space, the number of piles of finished products, and the dimensions of the packaged finished products were considered. The results showed that, with a storage cabinet for finished products, IKM Kerupuk Azizah improved products’ quality and hygiene so that consumers would have more confidence in purchasing the products. In addition, IKM Kerupuk Azizah also applied the Seiri, Seiton, Seiso, Seiketsu, and Shitsuke (5S) principles in their work environment to create a clean, healthy, and comfortable workplace.